A STUDY OF RESILIENCE AND PSYCHOLOGICAL WELLBEING AMONG ADOLESCENCES (International Journal of Food and Nutritional Sciences, 2022)
Adolescences who become resilient are inquisitive, brave, and trust their instincts. These children are more likely to take healthy risks because they don't fear falling short of expectations. Through resilience, they develop independence, efficient problem-solving skills and are better able to build and maintain interpersonal relationships. Hence, the resilience and psychological well-being and their relations in male and female adolescences were systematically measured and compared separately. For this, purpose 70 males adolescences and 70 females adolescences of Bihar were purposively selected and they were administered resilience questionnaire and psychological well-being scale. The t- test was applied to analyze the data. The results as follows: Significant difference between mean resilience cores of male and female adolescences was obtained. Significant difference between mean psychological well-being scores of male and female adolescences was obtained. The study aims in making the adolescences aware of the role of resilience and their harmful effect in personal life and the different coping strategies that can help them deal with the stressors in a better way, and thus maintaining their psychological well-being the review concludes with a summary of major research findings, as well as a consideration of future directions and implications for practice and policy.